Whey Protein and Its Components Lactalbumin and Lactoferrin Affect Energy Balance and Protect against Stroke Onset and Renal Damage in Salt-Loaded, High-Fat Fed Male Spontaneously Hypertensive Stroke-Prone Rats. Issue 4 (27th December 2019) - Singh, Arashdeep; Zapata, Rizaldy C; Pezeshki, Adel; Knight, Cameron G; Tuor, Ursula I; Chelikani, Prasanth K
ABSTRACT: Background: Whey protein (WH)-enriched diets are reported to aid in weight loss and to improve cardiovascular health. However, the bioactive components in whey responsible for causing such effects remain unidentified. Objective: We determined the effects of whey and its components [α-lactalbumin (LA) and lactoferrin (LF)] on energy balance, glucose tolerance, gut hormones, renal damage, and stroke onset in rats. Methods: Male spontaneously hypertensive stroke-prone (SHRSP) rats (age 8 wk) were fed isocaloric high-fat (40% kcal) and high-salt (4% wt/wt) diets (n = 8–10/group) and randomized for 8 wk to diets enriched as follows: control (CO): 15% kcal from egg albumin, 45% kcal from carbohydrate; WH: 20%kcal WH isolate + 15% kcal egg albumin; LA: 20% kcal LA  + 15% kcal egg albumin; or LF: 20% kcal lactoferrin + 15% kcal egg albumin. Measurements included energy balance (food intake, energy expenditure, and body composition), stroke-related behaviors, brain imaging, glucose tolerance, metabolic hormones, and tissue markers of renal damage. Data were analyzed by linear mixed models with repeated measures or 1-way ANOVA. Results: Diets enriched with WH, LA, or LF increased survival, with 25% of rats fed these diets exhibiting stroke-associated morbidity, whereas 90% of CO rats were morbid by 8 wk ( P  < 0.05). The nephritis scores of rats fed WH-, LA-, or LF-enriched diets were 80%, 92%, and 122% lower than those of COs ( P  = 0.001). The mRNA abundances of renin and osteopontin were 100–600% lower in rats fed WH-, LA-, or LF-enriched diets than in COs ( P  < 0.05). Urine albumin concentrations and albumin-to-creatinine ratios were 200% lower in rats fed LF-enriched diets than in COs ( P  < 0.05). Compared with COs, rats fed LF-enriched diets for 2–3 wk had food intake decreased by 29%, body weight decreased by 13–19%, lean mass decreased by 12–19%, and fat mass decreased by 20% ( P  < 0.001). Relative to COs, rats fed WH and LA had food intake decreased by 10% ( P  < 0.1), but COs had 12–45% lower weight than rats fed LA- and WH-enriched diets by 3 wk ( P  < 0.01). Compared with COs, rats fed WH-enriched diets increased energy expenditure by 7%, whereas, rats fed LA-enriched diets had energy expenditure acutely decreased by 7% during the first 4 d, and rats fed LF-enriched diets had energy expenditure decreased by 7–17% throughout the first week ( P  < 0.001). Rats fed LA- and LF-enriched diets had blood glucose decreased by 14–19% ( P  < 0.05) and WH by 9% ( P  = 0.1), relative to COs. Compared with COs, rats fed LF had GIP decreased by 90% and PYY by 87% ( P  < 0.05). Conclusion: Together, these findings indicate that whey and its components α-lactalbumin and lactoferrin improved energy balance and glycemic control, and protected against the onset of neurological deficits associated with stroke and renal damage in male SHRSP rats.